Electronic structure, reactivity, and Hirshfeld surface analysis of carvone. Issue 9 (September 2019) - Yankova, Rumyana; Dimov, Milen; Dobreva, Krasimira; Stoyanova, Albena
The density functional theory (at the B3LYP level using 6-311++G(2d, 2p) basis set) was used for the investigation of the geometry and electronic properties of the carvone. The electronic properties and chemical activity of the titled compound were investigated by means of several theoretical approaches, molecular electrostatic potential surface, natural bond orbital, and frontier molecular orbital analyses. It was established that the oxygen atom in the structure characterized the electrophilic reactivity; the positive regions are localized on the hydrogen atoms, which can be considered as possible sites for nucleophilic attack. A detailed analysis of the intermolecular interactions via Hirshfeld surface analysis and fingerprint plots revealed that the carvone structure is stabilized mainly by the formation of O. . .H/H. . .O hydrogen bonds. However, close contacts were established between C. . .H/H. . .C and H. . .H contacts.